Tinjauan Atas Upaya Penyelesaian Sengketa Lingkungan Hidup Di Luar Pengadilan Sesuai UU Nomor 23 Tahun 1997 Tentang Pengelolaan Lingkungan Hidup - Emilda Kuspraningrum; Mahendra Putra Kurnia (Jurnal Risalah Hukum, 2005)
Human being behavior very influence the continuity of human being prosperity and also the other mortal in an environment, positive human being behavior perhaps will affect positive also for continuity of environment, however if human being behavior instruct at negative behavior such as contamination or environmental mutilation perhaps will affect negativity for continuity of environment and harm other party. In This Case, contamination or environmental mutilation often cause incidence of environment dispute which in the end the harmed by party of effect the contamination or mutilation of environment will claim indemnation for grief which feeling of. Hitting problem of dispute of environment and indemnify, UU Nomor 23 Tahun 1997 about Pengelolaan Lingkungan Hidup provide alternative of solving of extrajudical dispute, which way of this looked into more effective, quickly and cheap compared to by the solving of through jurisdiction institute. Solving of this extrajudical dispute aim to to determine the level of indemnation and certain action utilize to guarantee do not recure of negative impact to environment. Key words : Environment,Environmental Dispute,The Parties,Extrajudicial Dispute Resolution, Service Institution